INSTABILITAS RENDEMEN CPO PADA INDUSTRI MINYAK SAWIT [CPO Yield Instability on Palm Oil Industry] - Fradana Subagya; Endy Suwondo (Jurnal Teknologi & Industri Hasil Pertanian, 2018)
The problem faced by the palm oil industry today is the instability of the Crude Palm Oil (CPO) yield.  The condition of Fresh Fruit Bunches (FFB) starting from the time of harvesting to transporting to the factory, including during stockpiling at the palm oil mill, is an influential factor affecting the yield of CPO.  This study aimed to find the factors causing instability of CPO yield in the palm oil industry.  I-MR control maps and fishbone diagrams were used to analyze the factors that cause low CPO yields.  From the data analysis for three years, the evidence of CPO yield was not statistically controlled.  The causative factor of CPO yield instability included the quality of raw materials, production equipment, character of workers, and environmental conditions, with the dominating factor was the low quality of raw materials.